Strategi Pengembangan Kompetensi Guru dan Staf dalam Manajemen SDM Pendidikan - Aida Raihani Subandi; Awalia Izza Ari Putri; Hilman Achmad Sanusi; Hesti Kusumaningrum (Edukasi Elita : Jurnal Inovasi Pendidikan, 2025)
In the era of globalisation and rapid technological development, developing the competencies of teachers and education staff is key to improving the quality of education. This article discusses various strategies for competency development in education human resource management (HRM), with a focus on teachers and education staff. Adopting an evidence-based approach identifies effective methods for training and professional development, including the utilisation of technology, online courses, and experiential learning. In addition, it explores the critical role of constructive feedback and continuous evaluation in the competency development process. The research underscores the importance of integration between HRM theory and daily educational practice to achieve optimal results. The results of this article are expected to provide practical guidance for educational institutions in designing effective development programmes to improve teacher and staff performance and advance the education system as a whole.